Analisis keragaan panel sandwich untuk rumah pra-pabrikasi - Naresworo Nugroho; Effendi Tri Bahtiar (Jurnal Ilmu Pertanian Indonesia, 2010)
In the last five years, several earthquakes struck several places in Indonesia and thousands of people died caused of their masonry house. Therefore, the idea of bamboo utilization in the form of structural sandwich panel components for anti-seismic pre-fabrication house is one of appropriate way out. This research describes the performance and behavior of engineered structure wooden-bamboo sandwich panel in full sized test. The wall frame being use were meranti wood, this frame attached by plywood as face and back, then 5 em bamboo cutting as core; the fastener used in this study were isocyanate resin and nails. This study carried out by experimental data of full scale structural tests on shear wall (ISO 22452). These result showed that the seismic reliability of the wall frame system made of bamboo sandwich panel was appropriate and will be useful for prefabrication houses as anti-seismic and environment friendly residential building.